2021
DOI: 10.18632/aging.203472
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a ferroptosis-related gene signature predictive of prognosis in breast cancer

Abstract: Ferroptosis, a novel form of regulated cell death, is closely associated with the occurrence and development of malignant tumors. Here, we utilized a bioinformatics approach to identify ferroptosis-related genes to establish a robust and reliable prognostic signature in breast cancer (BC). Univariate Cox regression and LASSO regression analyses of patient’s survival and gene expression data identified a prognostic signature consisting of 10 ferroptosis-related genes (FRGs). The signature demonstrated a favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Recent studies have used bioinformatics methods to identify genes related to iron death. These studies can help identify potential disease-related key genes [ 16 ], predict disease prognosis models [ 17 ], discover potential biomarkers and therapeutic targets [ 18 ], and provide new strategies for individualized treatment. Liang et al found that most genes related to iron death are differentially expressed between liver cancer and adjacent normal tissues, and iron death-related gene markers can be used to predict the prognosis of liver cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used bioinformatics methods to identify genes related to iron death. These studies can help identify potential disease-related key genes [ 16 ], predict disease prognosis models [ 17 ], discover potential biomarkers and therapeutic targets [ 18 ], and provide new strategies for individualized treatment. Liang et al found that most genes related to iron death are differentially expressed between liver cancer and adjacent normal tissues, and iron death-related gene markers can be used to predict the prognosis of liver cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…FRGs-based signatures had been identified with prognostic values in colon cancer, [ 51 ] lung adenocarcinoma, [ 52 , 53 ] gastric cancer, [ 54 ] breast cancer, [ 55 ] and bladder cancer. [ 21 , 56 ] And nomograms built by FRGs for predicting survival probabilities had already been used in lung adenocarcinoma and oral squamous cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the outcome of the independent prognosis analysis, we used the independent prognostic factors to plot the nomogram [ 28 ]. The Harrell' concordance index (C-index) and the calibration curve about the patients' long-term survival probability (3- and 5-year probability) examined the accuracy and divergence of the nomogram.…”
Section: Methodsmentioning
confidence: 99%